PENGARUH DIMENSI EFEKTIVITAS KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN RUMAH SAKIT PERMATA BUNDA YOGYAKARTA - Farlianto, Farlianto Farlianto (Universitas Negeri Yogyakarta, 2015)
This study is aimed to investigate the effect of the leadership effectivities on the job satisfaction of the staff on Permata Bunda hospital in Jogjakarta. Regression analysis is used to find out the effect of the leadership effectivities on the job satisfactio. The result showed that of the leadership effectivities dimension are effect on the job satisfaction of the staff on Permata Bunda hospital in Jogjakarta.